DNA Barcoding of Anchovy in Tuban Regency as Database of Indonesian Marine Genetic Diversity - Joesidawati, Marita Ika; Nursalim, Nining; Kholilah, Nenik; Kurniasih, Eka Maya; Cahyani, Ni Kadek Dita; Ambariyanto, Ambariyanto (Marine Science Department Diponegoro University, 2023)
Anchovy is the main catch and the primary consumption of coastal communities in Indonesia, and its production shows an increase of more than 10% in 2021. Tuban district, in East Java, Indonesia is part of the WPP 712 (Wilayah Pengelolaan Perikanan or Fisheries Management Area) and highly produces anchovies’ fisheries. Anchovy has a small size, making it difficult to identify morphologically. This study aimed to genetically identify anchovy samples obtained from North Java (Tuban) waters. Molecular identification was conducted by utilizing Cytochrome Oxidase Subunit I (COI) gene using jg-HCO and jg-LCO primers. This study observed 12 individual samples with 623 base pair sequence length. Five species were obtained, namely four species of anchovies (Encrasicholina heteroloba, Encrasicholina punctifer, Stolephorus waitei, and Stolephorus insularis) and one species of sardines (Dussumieria elopsoides) with 99.84-100% similarity to NCBI sequences data. Anchovies typically have a streamlined body with a slightly compressed shape. Anchovies have cycloid scales, which are smooth-edged and relatively small, ranging from a few centimeters to around 20 centimeters in length. Some of the genus from the Anchovy group are Encrasicholina and Stolephorus. The phylogenetic tree reconstruction leads into four clades with a genetic distance between clades of 17,9-24,5 %. This research provides methods and data on the genetic diversity of anchovies taxa caught in Tuban, East Java. The findings are expected to support promoting new standards for healthier and more sustainable anchovy stocks in the country. Overall, this study contributes to providing valuable insights for fisheries management and conservation efforts in Indonesia.